2020
DOI: 10.1002/smi.2971
|View full text |Cite
|
Sign up to set email alerts
|

Salivary cortisol and alpha‐amylase daily profiles and stress responses to an academic performance test and a moral cognition task in children with neurodevelopmental disorders

Abstract: There is evidence that children with neurodevelopmental disorders may exhibit atypical responses to stress and alterations in concentrations and diurnal secretion of stress hormones. We assessed diurnal profiles and stress responses of salivary cortisol and alpha‐amylase (sAA) in children with attention‐deficit hyperactivity disorder (ADHD), autism spectrum disorder (ASD) and specific learning disorder (SLD) compared to typically developing children (TD). A total of 157 children of both sexes, aged between 6 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(41 citation statements)
references
References 65 publications
1
34
2
Order By: Relevance
“…However, these factors are often less mentioned in most of the studies. We have carried out a qualitative examination on the aforementioned factors in the included studies of our meta-analysis (see Table 1 and Supplementary Table S3 ) and found that although most of the studies [ 3 5 , 20 , 22 26 , 29 34 , 36 , 37 ] reported ADHD medication use status except for Jansen et al [ 28 ] and Ma et al [ 35 ], none mentioned about the 21-hydroxylase genetic mutations. In addition, although most of the included studies, other than those collected awakening salivary cortisol levels [ 3 , 20 , 22 , 23 , 26 , 32 ], did not report the resting time required prior to the sample collection, however, they did ask the patients to have at least 30 min to a 90 min gap between brushing their teeth, eating/ drinking and the sample collection; [ 4 , 5 , 20 , 24 , 25 , 31 , 34 37 ] and at least a 90 min to a 24 h restriction of strenuous exercises prior to the sample collection [ 5 , 20 , 25 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these factors are often less mentioned in most of the studies. We have carried out a qualitative examination on the aforementioned factors in the included studies of our meta-analysis (see Table 1 and Supplementary Table S3 ) and found that although most of the studies [ 3 5 , 20 , 22 26 , 29 34 , 36 , 37 ] reported ADHD medication use status except for Jansen et al [ 28 ] and Ma et al [ 35 ], none mentioned about the 21-hydroxylase genetic mutations. In addition, although most of the included studies, other than those collected awakening salivary cortisol levels [ 3 , 20 , 22 , 23 , 26 , 32 ], did not report the resting time required prior to the sample collection, however, they did ask the patients to have at least 30 min to a 90 min gap between brushing their teeth, eating/ drinking and the sample collection; [ 4 , 5 , 20 , 24 , 25 , 31 , 34 37 ] and at least a 90 min to a 24 h restriction of strenuous exercises prior to the sample collection [ 5 , 20 , 25 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have carried out a qualitative examination on the aforementioned factors in the included studies of our meta-analysis (see Table 1 and Supplementary Table S3 ) and found that although most of the studies [ 3 5 , 20 , 22 26 , 29 34 , 36 , 37 ] reported ADHD medication use status except for Jansen et al [ 28 ] and Ma et al [ 35 ], none mentioned about the 21-hydroxylase genetic mutations. In addition, although most of the included studies, other than those collected awakening salivary cortisol levels [ 3 , 20 , 22 , 23 , 26 , 32 ], did not report the resting time required prior to the sample collection, however, they did ask the patients to have at least 30 min to a 90 min gap between brushing their teeth, eating/ drinking and the sample collection; [ 4 , 5 , 20 , 24 , 25 , 31 , 34 37 ] and at least a 90 min to a 24 h restriction of strenuous exercises prior to the sample collection [ 5 , 20 , 25 , 35 ]. What is more striking is that only 3 studies [ 5 , 20 , 25 ] asked their participants not to drink alcohol or smoke prior to the sample collection or mentioned substance use disorder in the exclusion criteria, although about more than half the studies [ 3 , 20 , 24 , 25 , 30 – 32 , 34 , 35 , 37 ] included in the meta-analysis enrolled teenagers with age ≥13, a population relatively at risk for substance use.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In one ADHD study, a lower evening and diurnal sAA secretions in response to stress were noted [ 54 ]. It should be remembered that the salivary glands are innervated by both the sympathetic and parasympathetic parts of the autonomic nervous system (ANS).…”
Section: Discussionmentioning
confidence: 99%